2015
DOI: 10.4172/2324-9080.1000217
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Caffeine on Strength Performance in Trained and Untrained Individuals

Abstract: Objective: The primary aim of this study was to compare the acute effects of a caffeine based supplement on the strength performance of trained and untrained individuals with a secondary investigation into the effects of a placebo.Method: Seven resistance trained (>6 months) and seven untrained (<6 months) males (mean ± SD: age: 21 ± 3 y, mass: 75.2 ± 11.3 kg, height: 176 ± 6 cm) consumed either caffeine (CAF) (5 mg.kg.bw -1 ), placebo (PLA) or nothing (CON) 60 minutes prior to 1 RM squat measurements in a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
0
28
4
4
Order By: Relevance
“…The only study included in the review by Grgic et al 11 that directly compared the effects of caffeine between trained and untrained individuals reported ergogenic effects of caffeine in untrained but not in trained individuals. 59 These results are in contrast to the common belief about greater responsiveness to caffeine in trained individuals. Future work is needed on this topic (for additional discussion on this topic see the reviews by Tallis et al 62 and Burke 63 ).…”
Section: Optimal Timing Of Caffeine Ingestionmentioning
confidence: 70%
See 1 more Smart Citation
“…The only study included in the review by Grgic et al 11 that directly compared the effects of caffeine between trained and untrained individuals reported ergogenic effects of caffeine in untrained but not in trained individuals. 59 These results are in contrast to the common belief about greater responsiveness to caffeine in trained individuals. Future work is needed on this topic (for additional discussion on this topic see the reviews by Tallis et al 62 and Burke 63 ).…”
Section: Optimal Timing Of Caffeine Ingestionmentioning
confidence: 70%
“…While it has been suggested that trained individuals might respond better to caffeine ingestion, the current evidence on this topic is scarce and conflicting. [59][60][61] The meta-analyses that have tried to explore this matter were commonly performed on a limited number of studies. For example, Grgic et al 11 only included seven and four studies for their subgroup analysis of the effects of caffeine among trained and untrained individuals, respectively.…”
Section: Optimal Timing Of Caffeine Ingestionmentioning
confidence: 99%
“…The only other study to compare trained and untrained subjects in the same design, that also observed caffeine-induced improvements in performance, reported that untrained and trained subjects experienced similar improvements in 10-km cycling performance [15], which again is in contrast to the prior mentioned meta analysis. The other two studies concluded that training status had no effect on time-to-fatigue [16] or peak strength [17], although there was no main effect of caffeine in either study. The lack of a significant ergogenic effect of caffeine in these studies (i.e., experimental models that did not detect a beneficial effect of caffeine) makes it impossible to tease out the impact of training levels.…”
Section: Introductionmentioning
confidence: 99%
“…Mizuno et al [ 106 ] reported that trained men have greater adenosine A 2a receptor densities than untrained subjects; it might be that this increase in adenosine receptor density in trained individuals allows greater binding of caffeine to these receptors, increasing the magnitude of the acute improvements in exercise performance following caffeine ingestion. This idea, however, remains speculative; in contrast to the work by Collomp et al [ 24 ] and Astorino et al [ 97 ], other studies report that caffeine ingestion may produce similar performance benefits in both trained and untrained (or recreationally trained) individuals [ 107 , 109 ]. Moreover, in some cases, caffeine ingestion enhanced performance in untrained but not in trained individuals [ 109 ]; see Table 2 for a summary of these studies.…”
Section: What Else Do We Need To Know About Caffeine In Sport?mentioning
confidence: 99%
“…This idea, however, remains speculative; in contrast to the work by Collomp et al [ 24 ] and Astorino et al [ 97 ], other studies report that caffeine ingestion may produce similar performance benefits in both trained and untrained (or recreationally trained) individuals [ 107 , 109 ]. Moreover, in some cases, caffeine ingestion enhanced performance in untrained but not in trained individuals [ 109 ]; see Table 2 for a summary of these studies.…”
Section: What Else Do We Need To Know About Caffeine In Sport?mentioning
confidence: 99%